1990
DOI: 10.1192/bjp.157.5.735
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Soft Signs in Schizophrenia

Abstract: A standardised clinical examination which focused on neurological soft signs (NSS) was used by a neurologist blind to diagnosis to assess the presence of neurological soft signs. A comparison of NSS score was made among three groups of subjects consisting of 58 DSM-III schizophrenics, 31 of their healthy first-degree relatives and 38 normal controls. The schizophrenic group had significantly higher NSS total scores than normal controls but did not differ significantly from their first-degree relatives' group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(101 citation statements)
references
References 19 publications
1
98
2
Order By: Relevance
“…However, the clinical and etiological significance of ND is unclear. Interestingly, in this context, there is a significant association between increased ND in schizophrenics and their global severity of illness (Ismail et al, 1998); This condition was also found in the mentally healthy first-degree biological relatives of schizophrenics (Ismail et al, 1998;Kinney et al, 1986;Rossi et al, 1990;Cantor-Graae et al, 1994;Egan et al, 2001).…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…However, the clinical and etiological significance of ND is unclear. Interestingly, in this context, there is a significant association between increased ND in schizophrenics and their global severity of illness (Ismail et al, 1998); This condition was also found in the mentally healthy first-degree biological relatives of schizophrenics (Ismail et al, 1998;Kinney et al, 1986;Rossi et al, 1990;Cantor-Graae et al, 1994;Egan et al, 2001).…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…Interestingly, there is a significant association between increased ND in schizophrenics and their global severity of illness (Ismail et al, 1998); this condition was also found in the mentally healthy first degree biological relatives of schizophrenics (Ismail et al, 1998;Kinney et al, 1986;Rossi et al, 1990;Cantor-Graae et al, 1994;Egan et al, 2001).…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…The reliable assessment of neurological soft signs provides a useful index of neurodevelopmental disruption. A number of batteries are used to assess neurological impairment in schizophrenia including the Neurological Evaluation Scale (NES; Buchanan & Heinrichs, 1989), the Cambridge Neurological Inventory (Chen et al, 1995), the Woods Scale (Woods, Kinney, & Yurgelun-Todd, 1986), the Heidelberger Scale (Schroder et al, 1991), the Condensed Neurological Examination (Rossi et al, 1990), and the Modified Quantified Neurological Scale (Convit, Jaegar, Lin, Meisner, & Volvaka, 1988). The NES is the most widely used structured examination to assess neurological impairment in schizophrenia.…”
Section: Neurological Soft Signsmentioning
confidence: 99%